Comparative hypocholesterolemic effect of ethanolic extract of green tea (Camellia sinesis) with atorvastatin on experimentally induced hypercholesterolaemic rats - Mustafa, Nafisa; Haq, Md Enamul; Ahmed, Farzana; Saha, Shusmita; Alam, Md Khorshed (Journal of Dhaka National Medical College & Hospital, 2018)
Background: Ethanolic extract of green tea thought to be play an important role in reducing lipid level in experimentally induced hypercholesterolaemic rats. Objectives: To evaluate the lipid lowering effect of green tea on experimentally induced hyperlipidemic rats. Study design: An experimental study was done to observe the hypocholesterolaemic effect of green tea (Camellia sinesis) on experimentally induced hypercholesterolaemic rats. Place and period of study: The study was conducted during july 2015 to june 2016 in the Department of Pharmacology & Therapeutics, Dhaka Medical College, Dhaka. Material and Method: A total number of 42 healthy rats (Norwegian Strain) were included in this study involving 6 groups. Atorvastatin was used as reference drug for comparison. To induce hypercholesterolemia, rats were fed fatty diet (1.5ml olive oil +1 % cholesterol). The experimental group received ethanolic extract of green tea in a dose 100mg/kg and 200mg/kg and atorvastatin 0.14mg/kg were used to see the hypercholesterolemic effects in hyperlipidemic rats. Each group treated for 10 days and sacrificed on 11th day. Serum cholesterol level was measured by using lipid profile kits. Result: Serum cholesterol level of the groups of rats treated with 100mg/kg, 200mg/kg ethanolic extract of green tea and 1% cholesterol diet were decreased than that of hypercholeterolaemic control group. Reduction of cholesterol level was similar to hypercholesterolaemic rats treated with 0.14mg/kg atorvastatin for 10 days. The mean ±SD of serum TCL level in group C, D, F were 141.50 +2.60, 122.27 ±3.44, 73.32 ± 3.20 and 72.61 ± 3.19 mg/dl respectively. It was observed that serum TCL level decreased in all green tea and atorvastatin treated groups compared ith the hyperlipidemic control group (group C), But changes were highly significant in group D, E and F (p<0.05, p<0.001, p<0.001). Conclusion: From the result, it can be concluded that Green tea (camelia sinesis) exhibits significantly hypolipidemic effect. Several double blinded randomized controlled clinical trial should be done after careful toxicology study. Then it could be act as a potent hypolipidaemic agent for therapeutic use. J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 10-13